The employment of jet V-STOL aircraft at sea - Kinch, M. J. (Cranfield University, 1981)
The means by which the Royal Navy will continue to operate fixed-wing aircraft at sea is by employing VTOL or· given an aid to-take-off, STOVL aircraft. The aid being ' brought into service is -the Skijump, which permits a large increase in payload over unassisted VTOL. The effectiveness of skijump increases with its exit angle up to about 40°, but other considerations of size and ungainliness set a practical lim~tation nearer to 20°. The endspeeds required for ballistic launch off a skijump could be achieved or-enhanced by the use of assistance by catapult or rocket motor. Both of these would call for the initiation of programmes of full research and development, while the skijump, capable of conferring. equivalent performance if it is long enough, already exists. The· smallest number of aircraft in an airgroup able to keep up a useable flying task is three. A vessel big enough to mount three aircraft together with the gear necessary to support and arm them would be big enough to mount a skijump as well. Its size is dictated too by the sea conditions in which it is expected to keep operational. The vessel in question should be a displacement ship, either conventional (e.g. large frigate) or unconventional (e.g. Small Waterplane Area Twin Hull). There is no role here for either hovercraft or hydrofoil. Commitment to the skijump.in the ship means commitment to vectored-thrust as a means of propulsion in the next aircraft~ When specified it must be compatible with existing skijump decks, and it should be single-engined. Its targets for Reliability and Maintainability mµst be wholly related to the Availability called for, and must be given equal prominence with performance.